Empowerment of Satlinmas in Improving Public Order and Security - Winarko, Arief Dwi; Mursyidah, Lailul (Indonesian Journal of Cultural and Community Development, 2025)
The general background highlights the growing need for community involvement in safeguarding human rights and maintaining social stability, particularly in the context of regional apparatus empowerment. The specific background focuses on the role of Satlinmas in Candi District, where community members are organized to take an active part in protecting citizens against human rights violations. Despite existing research on community empowerment, there remains a knowledge gap regarding the effectiveness of Satlinmas in achieving these goals. This study aims to investigate how Satlinmas empowerment contributes to maintaining public order and security through a framework called Tri Bina, which encompasses Human Development, Business Development, and Environmental Development. The results indicate that Satlinmas has successfully enhanced community capacity through training and education, supported local businesses by ensuring a conducive environment for economic activities, and engaged in environmental preservation efforts. The novelty of this research lies in its comprehensive approach to community empowerment, emphasizing the interconnectedness of various developmental aspects. The implications of these findings underscore the importance of integrating community protection units into broader public safety strategies, highlighting the potential for improved community resilience and collaboration in safeguarding rights and maintaining order. Highlights: Community protection units improve public order and security. Tri Bina framework enhances human, business, and environmental development. SATLINMAS promotes community engagement in safety and environmental cleanliness. Keywords: Empowerment, Security, Environment, Community, Business